A NEW FINDING ON THE OCCURRENCE OF GOLDEN GECKO (CALODACTYLODES AUREUS) IN THE ROCK BOULDERS NEAR VELLORE TOWN - KUMAR, N.V.NANDA; M.RAJASEKHAR, (The Bioscan, 2007)
Golden geckos (Calodactylodes aureus) are reported for the first time in the rock boulders near Vellore Town ,North Arcot district of Tamilnadu,India . Vellore Town is surrounded by small hillocks with huge boulders. Those hillocks which are elevated at 50 to 100 meters are locations. A survey was made within fifteen kilometers radius towards east of Vellore town .Surprisingly golden geckos are observed in these locations contrary to the habitat described earlier .Hence the report emphasizes that golden geckos can also be seen in dry ,drought and high temperature zones where huge rock boulders are present and not only in the mountains of high altitudes with high rainfall and humidity.